Understanding the Cognition Process of the Students using the Internet as a Learning Resource - Husniyatus Salamah Zainiati (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2017)
This study aims to investigate how students search and process the information found on the Internet to meet the needs of their academic tasks as well as how they view such information compared to printed materials. The study was conducted targeting the student teachers at Primary School Teacher Education (PGMI) Program and Kindergarten Teacher Education Program (PGRA) in State Islamic University Sunan Ampel Surabaya. Such information search and processing are then later viewed through the lens of Blooms’ taxonomy. A qualitative method using the phenomenological approach is adopted in the study. Nine student participants of 1st, 2nd, 3rd-year classes were interviewed. The study indicates that the presence of the Internet as a source of learning has not shifted the role of the textbook as a primary source of information for the students while working on their academic assignments. It was revealed that the information search activities on the Internet have facilitated students to experience the four domains of the learning process in Bloom's Taxonomy.